PENGEMBANGAN MEDIA PEMBELAJARAN PALIPA PADA MATERI MENGENALI SIMBOL PANCASILA UNTUK SISWA KELAS II SEKOLAH DASAR - Wedar Puji Marta, Trias; Abdul Aziz Hunaifi; Rian Damariswara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the fact that in learning Civics, the material is recognizing Pancasila symbols, many students do not understand the material, this can be seen when students cannot answer questions given by the teacher. Students' lack of understanding in the material of recognizing Pancasila symbols is also caused by teachers using more lecture methods. This can make students not interested in the material presented by the teacher. The lack of development of the media used in learning activities regarding recognizing Pancasila symbols can reduce students' interest in learning. As a solution to the problems above, it is necessary to develop the PALIPA learning media